The allelopathic effects of Amaranthus on seed germination, growth and development of vegetables. Issue 4 (2nd October 2018) - Prinsloo, Gerhard; Du Plooy, Christiaan Phillipus
ABSTRACT: Amaranthus is a versatile plant used as a food, but it is also a recognised weed due to its competitive ability. Amaranthus is very nutritious and preferred by rural communities as a leafy vegetable, but it also contains anti-nutritional components and there are reports of allelopathic activity. This study investigated the effects of Amaranthus on seed germination, and the effects of Amaranthus grown in pots and in the field on follow-up crops planted in the same soil. Extracts of the whole plant, stems, leaves, flowers and roots of Amaranthus exhibited severe inhibition of seed germination of vegetables, as well as of weed seeds of Conyza bonariensis . Significant allelopathic effects were observed on tomato seedlings in the pot experiment with reduced growth in two of the treatments. However, no significant effects were observed in any of the field trials. All of the Amaranthus extracts exhibited very high electrical conductivity (EC) value. In a dilution experiment, the diluted extracts exhibited lower EC values, with no or limited seed germination at concentrations higher than 3.12 mg ml −1 and corresponding EC value of 2.1 mS cm −1 . The high EC values that were associated with the allelopathic effect, possibly resulted from allelochemicals in the plant, but these were not identified in this study. The origin and persistence of the allelopathic effect warrant further research to determine the risks for agricultural crops.